DIGITAL ECONOMY: AN ENTREPRENEURSHIP APPROACH - Rauf, Rusdiaman (Bisnis-Net, 2025)
This article aims to explore the role of the digital economy in the field of entrepreneurship. The approach of this research is qualitative with the Systematic Literature Review (SLR) method. The conclusion of this article, (i) the digital economy has driven innovation in the field of entrepreneurship, such as addressing global challenges and creating new markets. (ii) Digital Economy creates digital entrepreneurship which plays an important role in improving the welfare of business actors. (iii) The digital economy creates social inclusion in the Society